Differential expression of CD150/SLAMF1 in normal and malignant b cells on the different stages of maturation - Gordiienko, I.M.; Shlapatska, L.M.; Kovalevska, L.M.; Sidorenko, S.P. (Experimental Oncology, 2016)
Background: Within B-cell lineage cell surface receptor CD150/SLAMF1 is broadly expressed starting from pre-B cells with upregulation toward plasma cells. However, expression of CD150 is rather limited on the surface of malignant B cells with the block of differentiation at the different stages of maturation. The aim of our work was to explore CD150 expression both on protein and mRNA levels with the emphasis on CD150 isoforms in malignant B-cell lines at the different stages of maturation in comparison with their normal B cell counterparts. Materials and Methods: Studies were performed on normal tonsillar B-cell subpopulations, Blymphoblastoid cell lines, malignant B-cell lines of different origin, including pre-B acute lymphoblastic leukemia, Burkitt’s lymphoma, Hodgkin’s lymphoma, and multiple myeloma. Protein CD150 expression was assessed by western blot analysis and the expression level of CD150 isoforms was evaluated using qRT-PCR. Results: Despite the similar CD150 expression both on mRNA and protein levels in normal B-cell subsets and B-lymphoblastoid cell lines, malignant B-cell lines demonstrated substantial heterogeneity in CD150 expression. Only Hodgkin’s lymphoma cell lines, Burkitt’s lymphoma cell lines BJAB and Raji, and also pre-B cell line BLIN-1 expressed CD150 protein. At the same time total CD150 and mCD150 mRNA was detected in all studied cell lines excluding pre-B cell line REH. The minor sCD150 isoform was found only in Hodgkin’s lymphoma cell lines and Burkitt’s lymphoma cell line Raji. The nCD150 isoform was broadly expressed in tested B cell lines with exception of REH and Daudi. Conclusion: Malignant Bcell lines at the different stages of maturation only partially resemble their normal counterparts by CD150 expression. In malignant B-cell lines, CD150 expression on mRNA level is much broader than on protein level. CD150 isoforms are differentially expressed in normal and malignant B cells with predominant expression of mCD150 isoform.